2023
DOI: 10.12659/msm.939618
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Psychological Symptoms and Self-Esteem Levels Before and After Stomach Botox Treatment

Abstract: Background:Obesity is an exponentially increasing public health problem all over the world. When obesity is treated, many healing states begin to occur in obese individuals. Stomach Botox is also frequently used among non-surgical treatment methods. This prospective study examined the relationship between psychological symptoms and self-esteem levels before and after stomach Botox treatment. Material/Methods:We administered a survey to gather baseline information, and used the form, Brief Symptoms Inventory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Apart from its obvious benefits of shorter durations, less costly, fewer complications, a study reported that patients post-BTA injections felt less anxiousness, positive personality, less hostility than before the procedure [ 21 ]. However, the patients reported higher levels of depression post-injections, which was found to be statistically non-significant.…”
Section: Are Botulinum Injections Effective In Weight Loss?mentioning
confidence: 99%
“…Apart from its obvious benefits of shorter durations, less costly, fewer complications, a study reported that patients post-BTA injections felt less anxiousness, positive personality, less hostility than before the procedure [ 21 ]. However, the patients reported higher levels of depression post-injections, which was found to be statistically non-significant.…”
Section: Are Botulinum Injections Effective In Weight Loss?mentioning
confidence: 99%